2005
DOI: 10.1024/0300-9831.75.5.357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increased Dietary Protein and Energy on Composition and Functional Capacities of Blood Mononuclear Cells from Vaccinated, Neonatal Calves

Abstract: Effects of increased protein and energy provided by an intensified milk replacer on the antigen-specific, cell-mediated immune response of the neonatal calf were examined. Calves were fed a standard (0.45 kg/day of a 20% crude protein, 20% fat milk replacer; n=11) or intensified (1.14 kg/day of a 28% crude protein, 20% fat milk replacer; n=11) diet from 0 to 6 weeks of age. All calves were vaccinated with Mycobacterium bovis bacillus Calmette-Guerin (BCG) at 1 week of age. The daily weight gain of intensified-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Conversely, small calves with a low IGF-I concentration, indicative of low energy intake, were perhaps more susceptible to infections and thus at an increased risk of dying. The effect of increased protein and energy on the antigen-specific, cell-mediated immune response of the neonatal calf has previously been examined (Foote et al, 2005). Increased dietary protein and energy had subtle effects on the composition and functional capacities of peripheral blood mononuclear cell populations; further research is needed to determine if these minimal effects influence the calf's susceptibility to infectious disease, as speculated in our study.…”
Section: Discussionmentioning
confidence: 87%
“…Conversely, small calves with a low IGF-I concentration, indicative of low energy intake, were perhaps more susceptible to infections and thus at an increased risk of dying. The effect of increased protein and energy on the antigen-specific, cell-mediated immune response of the neonatal calf has previously been examined (Foote et al, 2005). Increased dietary protein and energy had subtle effects on the composition and functional capacities of peripheral blood mononuclear cell populations; further research is needed to determine if these minimal effects influence the calf's susceptibility to infectious disease, as speculated in our study.…”
Section: Discussionmentioning
confidence: 87%
“…In another meta-analysis, a calf's motivation to feed was a better predictor of health and performance than its colostrum passive transfer status (Bateman et al, 2012). This motivation to consume solid foods at an early age may influence HPN-calves' immune systems because they had less ex vivo innate immune responses before weaning, but after weaning, ex vivo immune measures did not differ from conventionally fed calves (Nonnecke et al, 2003;Foote et al, 2005Foote et al, , 2007Ballou, 2012;Obeidat et al, 2013;. Once HPN calves were no longer on a milk replacer diet, they also showed less signs of clinical sickness, faster inflammatory responses, and speedier recovery than conventionally fed calves when challenged with aerosolized Mannheimia haemolytica or oral Salmonella enterica serotype Typhimurium Sharon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Not only do dairy cattle possess different performance characteristics than typical beef breeds, such as a slightly lower ADG and greater DMI across the feeding period due to larger maintenance requirements, Holsteins are also more susceptible to environmental stressors because of their thinner hide and hair coat and less subcutaneous fat ( Hulbert and Moisa, 2016 ). However, multiple studies have examined ex vivo immune factors and observed that after weaning, Holstein calves did not differ immunologically from their conventionally fed beef animal counterparts ( Nonnecke et al, 2003 ; Foote et al, 2005 , 2007 ; Ballou, 2012 ; Obeidat et al, 2013 ; Ballou et al, 2015 ). Nonetheless, we are not aware of any studies to date that have compared the effects of feedgrade CTC or OTC, or in combination with tulathromycin metaphylaxis, on Holstein steers entering the feedlot.…”
Section: Discussionmentioning
confidence: 99%